Implementing care coordination in a large dental care organization in the United States by upskilling front office personnel - Aubri M. Kottek; Kristin S. Hoeft; Joel M. White; Kristen Simmons; Elizabeth A. Mertz (BMC, 2021)
Abstract Background Care coordination is a key strategy used to improve health outcomes and efficiency, yet there are limited examples in dentistry. A large dental accountable care organization piloted care coordination by retraining existing administrative staff to coordinate the care of high-risk patients. Following the pilot's success, a formal "dental care advocate" (DCA) role was integrated system-wide. The goal of this new role is to improve care, patient engagement, and health outcomes while integrating staff into the clinical care team. We aim to describe the process of DCA role implementation and assess staff and clinician perceptions about the role pre- and post-implementation. Methods Guided by the Consolidated Framework for Implementation Research, semi-structured interviews with clinical and operational administrative staff and observation at the company-wide training session were combined with pre- and post-implementation electronic surveys. Descriptive statistics and mean scores were tested for significance between each survey sample (t-tests), and qualitative data were thematically analyzed. Results With preliminary evidence from the pilot and strong executive support, a dedicated leadership team executed a stepwise rollout of the DCA role over 6 months. Success was facilitated by an organizational culture of frequent interventions deployed rapidly through a centralized system, along with supportive buy-in from managerial teams and high staff acceptance and enthusiasm for the DCA role before implementation. Following implementation, significant changes in attitudes and beliefs about the role were measured, though managers held stronger positive impressions than DCAs. DCAs reported high confidence in new skills and dental knowledge post-implementation, including motivational interviewing and the ability to confidently answer patients' questions about their oral health. Overall, the fast-paced implementation of this new role was well received, although consistent and significant differences in mean attitudes between managers and DCAs indicate more work to fine-tune the role is needed. Conclusions Successful implementation of the new DCA role was facilitated by a strong organizational commitment to team-based dentistry and positive impressions of care coordination among staff and managers. Upskilling existing administrative staff with the necessary training to manage some high-risk patient needs is one method that can be used to implement care coordination efforts in dentistry.